The need of a system phantom for quantitative hybrid nuclear imaging of PET/CT: a systematic review - Hanafi, Muhammad Hafiz; Mohd Noor, Noramaliza; Ahmad Saad, Fathinul Fikri; Ramli, Saiful Hasley; Mohamed, Faizal; Musarudin, Marianie (Malaysian Medical Association, 2021)
Introduction: There has already been a rising demand in utilising phantom for hybrid Positron Emission Tomography/ Computed Tomography (PET/CT) scanner of nuclear imaging. This review further clarifies this topic and investigates how the previous research phantoms operated with the need for quantitative hybrid nuclear imaging of PET/CT while providing a relatively high image quality when it was performed. In this article, the necessity of previous and current phantom studies in hybrid nuclear imaging of PET/CT scanners is reviewed. Methods: PubMed and Google Scholar were systematically searched for the relevant studies by following the PRISMA 2009 checklist. A past decade literature search was conducted from 2010 until November 2020 to secure the relevance of the phantom study. Databases were recruited using keywords such as phantom, quantification, standardisation, harmonisation, image quality, standardised uptake value and multicentre study. However, all keywords were related to PET/CT. All abstracts and eligible full-text articles were screened independently, and finally, the quality assessments of this review were performed. Results: From the 200 retrieved articles, 80 were rejected after the screening of the abstracts and 35 after reading the full-text. The 20 accepted articles addressed the distribution of phantom types used in selected articles studies which were NEMA (67%), ACR (8%) and others (25%). The articles showed the various experimental studies, either phantom studies (35%) or phantom plus clinical studies (65%). For clinical studies (n = 829), the distribution of prospective studies was (n = 674) and retrospective studies was (n =155). The distribution of phantom pathway application showed the studies focused on 40% of reconstruction protocol studies, 30% of the multicentre and standardisation of accreditation program studies, and 30% of the quantification of uptake values studies. Conclusions: According to this review, the phantom study have a pivotal role in hybrid nuclear imaging of PET/CT either in technical aspects of the scanners (such as data acquisition and reconstruction protocol) or clinical characteristics of patients. In addition to this, the necessity to identify the suitable system phantoms to use within PET/CT scans by considering the continuous development of new phantom studies are needed. Researchers are encouraged to adopt efforts on phantom quantitative validation, including verification with clinical data of patients.